Study on Fuzzy Self-Tuning PID Internal Model Control Algorithm and Its Application - Zhang Ming-guang; Wang Peng; Wang Zhao-gang (CIS Workshops 2007 : 2007 International Conference on Computational Intelligence and Security Workshops : proceedings : 15-19 December, 2007, Harbin, Heilongjiang, China, 2007)
Through introducing 1/1 pade series to approximate the time delay unit and using the two steps design approach, the internal model control system can be changed into conventional PID unity feedback control system. Then used fuzzy inference to tune the PID parameters online, the fuzzy self-tuning PID internal model controller is realized. This controller combines the advantage of fuzzy control, internal model control and PID control. Fuzzy control is used to overcome the uncertainty of mathematical model of the real plant. Internal model control is used to resolve the large time-delay of the coke oven temperature control system. Simulation experiments have been done to coke oven temperature control system. Simulation results show that system adopted fuzzy self-tuning PID internal model control has smaller steady error, shorter adjusting time, smaller overshoot, faster rising time and comparatively strong robustness.